Pioneering Youth Movement : Pandawara Group and Kader Hijau Muhammadiyah in Advocating for Ecological Justice in Indonesia - Hendy Setiawan; Choironnisa Choironnisa; Ahmad Sholikin; Yendra Erison (Universitas Islam Darul Ulum Lamongan, 2025)
The purpose of this article is to analyze the positioning of the pioneer youth movements, namely Pandawara and KHM in Indonesia. The study of youth and ecology is an interesting study because so far the relationship between youth and ecology has not been well connected. However, in recent years it has been seen how the younger generation has begun to migrate towards the issues they raise. As a result of this issue migration activity, there is a tendency to strengthen the younger generation's issues in the field of ecology. This fact triggered the birth of various associations, groups, communities, youth movements or organizations which began to pay attention and concern to the ecological sector. This research uses a qualitative descriptive method. The author collected data using literature study steps. All data and facts are collected from various relevant literature in accordance with the main problem formulation that has been determined previously. The research results show that the birth of KHM and the emergence of the Pandawara Group are signs of the awakening of the younger generation where they have paid attention to ecological problems. The existence of this young generation has a central role in accelerating ecological justice in the future. The trend of the younger generation like KHM and Pandawara in the dynamic arena of the younger generation is a historical milestone that we never imagined that their positioning would be able to mobilize the strength of society to work together to build ecological awareness today.